Islamic Law Review on The Determination of Surrogate Heirs - Sofyan Mei Utama (UIN Sunan Gunung Djati Bandung, 2018)
The surrogate heirs position on Islamic laws in indonesia reflects a justice form in the inheritance distribution, and constitutes a relief to the inheritors of inheritance, which is called the pre-empitiv policy ie, in the testator life by distributing his property to the heirs or heirs substitute. In accordance with the objectives of Islamic law (maqashid al-syari'ah) is intended for the benefit of the ummah and the theorem of Al-Maslahah Al-Mursalah which is necessary for caution, avoid following harmful lusts. Then the problem is: What was underlies the surrogate heirs position in Islamic law and how it relates to the Maslahah Mursalah's theory in Islamic law. The result of the research shows that, the substitute heirs position in Islamic law is based on the Article 185; Islamic Law Compilation in Indonesia by adhering to the principle of monotheism, an obedience to God's rule by not forgetting Iltihad. And the relationship with Maslahah Mursalah theory which is tied to Tawheed is the basis of this theory, ie : seeking the benefit for Allah SWT. there are benefits that are covered in the objectives of syara, so regarding to the surrogate heirs is done by giving priority to the benefit